Seedling establishment of maize and the use of saline water in different soil types - Guelloubi R.; Hamdy A.; Sardo V. (Non-conventional water use: WASAMED project, 2005)
In a greenhouse of the Mediterranean Agronomic Institute of Bari, an experiment was conducted and consisted on the study of the response of 2 varieties of maize under 2 soil types (sandy-loam and sandy-clay), 8 salinity levels (FW, 2, 4, 6, 8, 10, 12 and 15 dS/m) and 3 treatments during the seedling establishment (A
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)